Pengetahuan Ibu dengan Kejadian ISPA pada Anak - Rina Melinda Dunggio; Sri A. Ibrahim; Rini W. Mohamad (Journal of Telenursing (JOTING), 2026)
This study aimed to determine the relationship between maternal knowledge and the incidence of ARI in children in the Dungingi Community Health Center (Puskesmas) in Gorontalo City. The study employed a cross-sectional approach. The results showed a significant relationship between maternal knowledge and ARI incidence, with a chi-square test showing a p-value of 0.013 (<0.05). In conclusion, maternal knowledge is a factor associated with ARI incidence in children. The better the mother's knowledge regarding ARI prevention and treatment, the lower the risk of ARI in children.   Keywords: Children, ARI Incidence, Maternal Knowledge